Differences in hepatitis A seroprevalence among geographical regions in Turkey - Ceyhan, M.; Yildirim, I.; Kurt, N.; Uysal, G.; Dikici, B.; Ecevit, C.; Celebi, S. (Wiley, 2008)
Hepatitis A is a worldwide vaccine-preventable infection. Recommendation of vaccination depends on the endemicity of the disease. The World Health Organization recommends universal hepatitis A vaccination in intermediate areas; however, there is no need of mass vaccination in high and low endemicity regions. Therefore, most of the countries are using a vaccination policy according to the endemicity characteristic representing the whole of the country. The endemicity of this infection varies due to sanitary and hygiene conditions and socioeconomic differences among the countries and in various regions of the same country. A sample of 1173 persons between the age of 0 and 91 years from nine randomly selected medical centres from five different geographical centres of Turkey were tested for the level of anti-hepatitis A virus (anti-HAV) immunoglobulin-G antibodies using an enzyme-linked immunosorbent assay. The overall prevalence of anti-HAV antibodies was 64.4% (1142/1173). While the rate of sero-positivity was over 80% in the 5-9 age group and more than 90% after 14 years of age in south-eastern and eastern regions, it was lower than 50% at the age of 5-9 years in central and western regions and remains under 80% in those areas. We conclude that the differences observed in HAV sero-positivity among various geographical regions in Turkey support a universal HAV immunization policy for children currently living in regions of intermediate endemicity.
Keywords: endemicity; geographical variation; hepatitis A virus; seroprevalence; vaccination